THE RELEVANCE OF STIMULATING INNOVATION COMPETENCE OF MANAGERIAL PERSONNEL IN POST-CRISIS CONDITIONS OF FUNCTIONING OF DOMESTIC ENTERPRISES - Ekaterina Alekhina; Valentina Parakhina (Вестник Северо-Кавказского федерального университета, 2022)
The article defines the importance of innovation in modern conditions of economic development. The indicators characterizing the consequences of the economic crisis are given. Application of innovations in activity of modern enterprises as the main factor of development of economy is proved. Definitions of key concepts on the topic of the study are given. The author shows the relationship between the level of innovative activity of enterprises and the competence of their managers in the field of innovation, which is based on a set of knowledge and motivational components that allow the head of the enterprise to effectively use the existing innovation potential.